Combined endoscopic-percutaneous treatment of upper gastrointestinal enterocutaneous fistula using vacuum therapy and resorbable plug insertion (Vac-Plug) - Marcus Kantowski; Karl Karstens; Pasquale Scognamiglio; Nathaniel Melling; Matthias Reeh; Jakob Izbicki; Thomas Rösch; Michael Tachezy (Scientific Reports, 2022)
Abstract After gastrointestinal resections, leakages can occur, persist despite conventional therapy and result in enterocutaneous fistulae. We developed a combination method using flexible endoscopic techniques to seal the enteric orifice with an absorbable plug in addition to a percutaneously and fistuloscopically guided open-pore film drainage (Vac-Plug method). We retrospectively searched our endoscopy database to identify patients treated with the outlined technique. The clinical and pathological data were assessed, the method analyzed and characterized and the technical and clinical success determined. We identified 14 patients that were treated with the Vac-Plug method (4 females, 10 males with a mean age of 56 years, range 50–74). The patients were treated over a time period of 23 days (range 4–119) in between one to thirteen interventions (mean n = 5). One patient had to be excluded due to short follow-up after successful closure. Seventy-seven percent (10/13) were successfully treated with a median follow-up of 453 days (range 35–1246) thereafter. No treatment related complications occurred during the therapy. The data of the analysis showed that the Vac-Plug therapy is safe and successful in a relevant proportion of the patients. It is easy to learn and to apply and is well tolerated. In our opinion, it is a promising addition to the armamentarium of interventional methods of these difficult to treat patients. Of course, its usefulness must be further validated in larger prospective studies.